Analisis Faktor Faktor yang Berhubungan dengan Kualitas Hidup Keluarga Dampak Pandemi COVID-19 - Prahardian Putri; Azwaldi Azwaldi; Imelda Imelda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the factors related to the quality of life of families affected by Covid 19. This type of research is quantitative descriptive analytic research using a cross-sectional design. The results showed that the characteristics of the participants: Age that affects the quality of life is the late adult family members aged 36-45 years (45.9%). The most influential and dominant participants were civil servants as many as 17 civil servants (45.9%) . The most dominant participant is Senior high school with a total of 16 female gender (43.2%). The results of this study were obtained based on data analysis carried out by univariate, bivariate and multivariate analysis. Keywords: Covid 19, Impact of family quality of life, Quality of life